Pemanfaatan Chatbot Berbasis Kecerdasan Buatan (AI) Untuk Memfasilitasi Maharah Kalam - Randy Randy (CV. SINAR HOWUHOWU, 2026)
This literature review examines the use of Artificial Intelligence (AI)-based chatbots as a medium to facilitate maharah kalam (Arabic speaking skills). The rapid development of natural language processing (NLP) technology has opened new opportunities for interactive language learning, especially in the context of Arabic language education. This study employs a systematic literature review method by analyzing 25 relevant research articles published between 2018 and 2024 from international and national databases. The review findings indicate that AI-based chatbots are capable of providing adaptive, interactive conversational practice, correcting pronunciation and grammar errors in real time, and enhancing student motivation and speaking confidence. Several platforms such as Mondly, Duolingo, and specialized Arabic chatbot applications have shown positive results in improving students' maharah kalam competencies. However, challenges such as limited dialectal support, insufficient cultural context understanding, and the digital divide remain obstacles to their optimal implementation. This study recommends that chatbots be integrated as supplementary learning tools within structured Arabic language learning curricula.